2007
DOI: 10.1002/jsfa.3118
|View full text |Cite
|
Sign up to set email alerts
|

Production of α‐amylase by Aspergillus oryzae As 3951 in solid state fermentation using spent brewing grains as substrate

Abstract: BACKGROUND: The optimisation of nutrient levels for the production of α-amylase by Aspergillus oryzae As 3951 in solid state fermentation (SSF) with spent brewing grains (SBG), an inexpensive substrate and solid support, was carried out using response surface methodology (RSM) based on Plackett-Burman design (PBD) and Box-Behnken design (BBD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 34 publications
0
15
0
2
Order By: Relevance
“…BSG, which was used in this study, was also observed to be a good substrate for fungal amyloglucosidase production. Xu et al (2008) concluded that impressive amount of alpha amylase was produced from Aspergillus oryzae with solid culture cultivation method on BSG. Solid-state fermentation favored the production of amyloglucosidase significantly in cassava peels and BSG (p<0.05).…”
Section: Effect Of Wastes On Amyloglucosidase Production By Fungal Ismentioning
confidence: 98%
“…BSG, which was used in this study, was also observed to be a good substrate for fungal amyloglucosidase production. Xu et al (2008) concluded that impressive amount of alpha amylase was produced from Aspergillus oryzae with solid culture cultivation method on BSG. Solid-state fermentation favored the production of amyloglucosidase significantly in cassava peels and BSG (p<0.05).…”
Section: Effect Of Wastes On Amyloglucosidase Production By Fungal Ismentioning
confidence: 98%
“…High-positive values of coefficient factor for these variables (11.14 for C 7 , 1.93 for C 2 9 C 7 and 1.09 for C 2 9 C 9 ) also suggest its significance. The R 2 value (coefficient of determination) closer to one denotes better correlation between the observed and predicted values (Xu et al 2008). R 2 for chitinase activity was calculated as 0.8228, which is close to 1 and can explain up to 82.28 % variability of the response.…”
Section: Optimization Of Significant Variables Using Response-surfacementioning
confidence: 99%
“…Certain yeast and mould strains isolated from various sources, though aerobic, offer considerable potential, since their secreted enzymes are partially adsorbed into the cell wall, thus providing a biomass rich in proteins, nucleotides, and vitamins, as well as a cell extract with hydrolytic activity [5][6][7][8][9]. Random hydrolysis of starch by alpha-amylases produces low-molecular-weight oligosaccharides and, eventually, maltotriose and maltose from amylose and limit dextrins, and maltose and glucose from amylopectin.…”
Section: Introductionmentioning
confidence: 99%